Effects of Alternate Sessions, Vicarious Therapy Pretraining, and Patient Self-Exploration with Hospitalized Mental Patients during Group Therapy - Truax, Charles B.; Wittmer, Joe; Wargo, Donald G. (Canadian Journal of Counselling and Psychotherapy, 2012)
No abstract avilable